APPENDICITIS IN NEONATES (≤28 DAYS OF LIFE): CLINICAL PRESENTATION AND DIAGNOSIS - Anna Dominiczak; Katarzyna Mazurek; Marta Brzęcka; Stanisław Rogiński; Miłosz Rogiński; Krzysztof Rogiński; Marek Wojciechowicz; Łukasz Chojnowski; Karolina Kryca; Ksawery Szlęzak (International Journal of Innovative Technologies in Social Science, 2026)
Neonatal appendicitis is an exceptionally rare condition associated with high morbidity and mortality, primarily due to delayed diagnosis and a nonspecific clinical presentation that overlaps with more common neonatal disorders. The aim of the study: This study aimed to systematically review recently reported cases of neonatal appendicitis with a focus on clinical presentation and diagnostic features. Materials and methods: A systematic review was conducted in accordance with PRISMA guidelines using PubMed and Google Scholar. Fifteen case reports met the inclusion criteria. Results: Abdominal distension was the most frequently reported presenting symptom. Classic signs of acute abdomen were often absent. Laboratory findings were nonspecific and preoperative diagnosis was uncommon. Ultrasonography provided supportive diagnostic information, while pneumoperitoneum on plain radiography often prompted urgent surgical intervention. In most cases, the diagnosis was established intraoperatively, frequently after appendiceal perforation. Conclusions: Neonatal appendicitis presents with nonspecific clinical and diagnostic features that commonly mimic necrotizing enterocolitis. Awareness of abdominal distension as a consistent sign and careful interpretation of imaging findings may support earlier recognition and timely surgical management of this rare but life-threatening condition.